Characterization and correction of the effects of hepatic iron on T1ρ relaxation in the liver at 3.0T - Qian, Yurui; Hou, Jian; Jiang, Baiyan; Wong, Vincent Wai‐Sun; Lee, Jack; Chan, Queenie; Wang, Yixiang; Chu, Winnie Chiu‐Wing; Chen, Weitian (Magnetic resonance in medicine, 2022)
Purpose Quantitative T1ρ imaging is an emerging technique to assess the biochemical properties of tissues. In this paper, we report our observation that liver iron content (LIC) affects T1ρ quantification of the liver at 3.0T field strength and develop a method to correct the effect of LIC. Theory and Methods On‐resonance R1ρ (1/T1ρ) is mainly affected by the intrinsic R2 (1/T2), which is influenced by LIC. As on‐resonance R1ρ is closely related to the Carr–Purcell–Meiboom–Gill (CPMG) R2, and because the calibration between CPMG R2 and LIC has been reported at 1.5T, a correction method was proposed to correct the R2 contribution to the R1ρ. The correction coefficient was obtained from the calibration results and related transformed factors. To compensate for the difference between CPMG R2 and R1ρ, a scaling factor was determined using the values of CPMG R2 and R1ρ, obtained simultaneously from a single breath‐hold from volunteers. The livers of 110 subjects were scanned to validate the correction method. Results LIC was significantly correlated with R1ρ in the liver. However, when the proposed correction method was applied to R1ρ, LIC and the iron‐corrected R1ρ were not significantly correlated. Conclusion LIC can affect T1ρ in the liver. We developed an iron‐correction method for the quantification of T1ρ in the liver at 3.0T.